Apprentissage Tridimensionnel d'une Langue. - THEURIAU, Frédéric-Gaël (Recherches en Langue et Littérature Françaises)
In the field of learning French as a Foreign or the Second Language (FLES), most of the research focuses on highly advanced didactic and pedagogical methods. However, they tend to conceal the necessary immersion which is undoubtedly linguistic and at the same time cultural and creative. They distort as well the interpersonal relationship between teachers and learners. The former, considered as interchangeable objects by more and more institutions and language schools, are forced to teach in a way that is too standardized, calibrated and sanitized. The latter, attracted by the openness of the guarantee of a miraculous service by these same institutions and schools, are reinforced in their role as customers with all the rights, including that of evaluating their teachers. All of them have functioned exclusively remotely since the beginning of health crisis of 2019-2022 in order to protect teachers in a good way. It is an increasingly common, institutionalized and widespread practice in Belgium, the seat of the European Union, to hire exclusively independent but very qualified, experienced, helpful and compulsive teachers who carry out the activity which is not secured and relevant to modern slavery. It is essential to take into consideration the human dimension when learning a living language so as not to let artificial intelligence distort certain civilizational values and become a mandatory interface between people. Several major arguments support the thesis of not dissociating language and culture while adding the already old idea of creativity. This awareness even invites us to go beyond the simple learning of a foreign language. We must consider the approach as a step towards otherness and return to the more conventional system of a real class where a teacher is supported, recognized and respected by both employers and students, adults of all nationalities with positions of responsibility in various branches of the European Commission and all the above mentioned have the obligation to speak French. Learning is the way used by the teacher to be understood and to transmit knowledge to learners. This requires knowledge in pedagogy and didactics. In order to promote this learning, teaching a language passes through a pedagogical organization which is interested in a practical way of considering the relationship between the teacher and the learners, then through didactics, the object of which focuses on the theory of reflection on the content of the knowledge which has to be transmitted. It all leads to the balance between how to transmit and what to transmit. A language corresponds to a linguistic system composed of graphically transcribable vocal signs which are in close connection with a human group and allow communication between its members. Culture concerns the values of the reference dispersed over several areas of the mind that constitute the common heritage of a human group and through which its members recognize themselves. Human creativity is the cognitive capacity that makes it possible to invent something new, whether in linguistic, artistic or technical production. At first glance, language, culture and creativity seem to belong to the separated spheres which enable to derive theories and models that can be studied distinctly in vitro. But the daily practical reality does not distinguish them one from the other in their use in vivo. Indeed, when a language disappears, the associated culture and creative productions vanish as well, and what remains of the language, culture and creativity belongs to history. This was the case for Latin, which became an ancient language still studied, or Gaulish, which became a dead language of which we know almost nothing. In fact, is learning a language without culture or creativity possible? The structuralist thesis, the different types of statements, the genetic code of words and the transcultural vision will help to see things more clearly. Structuralist linguistics, which inherited the developments of Ferdinand de Saussure, assimilates the linguistic sign to a psychic entity from two sides. The structuralist thesis demonstrates the cognitive ability to adapt to an ever-changing enunciative situation and to consider a text holistically. But the possibilities of producing the speech are endless and complex. Statements present a great deal of complexity that must be taken into account depending on whether the meaning is literal or figurative. Everything rests on the proportion between the denotation whose mechanical transcoding is feasible and the connotation whose translation cannot be literally transcoded. In addition, the word carries certain cultural traces of a civilization. Another proof of the cultural presence registered in the very genes of words was brought to light by the work of certain linguists. If it is possible to go back to the cultural source from the root of words and linguistic system, then language and culture are inseparable. To this, a third dimension can be associated with this binomial. The Tunisian-French-Canadian Hédi Bouraoui focused on the question of learning a language and knowing the culture of others in the 1970s. This is the meaning developed by Hédi Bouraoui who proposed a method of learning in two works, Créaculture I and II in order to show, among other things, the benefits of transculturality. Ultimately, the language should not be taught to a foreign learner without its cultural context so that it remains living and contextualized. The spoken or written language contains the culture of origin of the speaker. Dumézil and Benveniste demonstrated this very well. Unless you study linguistics to understand the mechanisms of a language, there is no reason not to learn it through cultural or even creative activities. Mechanical learning therefore does not need to be dominating except of course in the early stages for levels A1, A2, B1, even B2 which must assimilate all the tools of the language for an immediate and practical communicational application in everyday life. The Bouraouïan vision explains, even beyond expectations, the interest of preserving the cultural aspect recommended by the structuralists. Ultimately, learning a language is done by combining three dimensions at once: the linguistic system, creativity and culture. All themes are welcome, namely current events, geopolitics, literature, theatre, rights, media, history, Francophonie, linguistics, environment, sport, tourism, daily life, migration, diplomacy, youth and science. Each language teacher or a teacher of French as a foreign or second language has a great deal of resources to teach their own lessons as long as for the learners to progress and better understand the language of other people in a transcultural approach, and not in that of the American melting pot which aims at assimilation by the forced erasure of original singularities, nor in that of Canadian multiculturalism which generates ghettoization by setting aside individuals. Therein lie the seeds of a search for peace between men through this true construction of otherness. Civilizations, with their linguistic, cultural and creative dimensions, reflect the environment in which people who possess them live and are themselves shaped by their geographical environment above all. This observation is consistent with the concept of Kenneth White's geopoetics on the links between man and earth. Northern peoples do not function in the same way as African or Australian societies, nor do Far Eastern societies have the same practices as American or European societies. This is also true on a smaller scale: the Occitan and Franco-Provençal regions have stronger identities than the rest of France.